Odpowiedzi

Najlepsza Odpowiedź!
2010-01-16T13:08:01+01:00
A.) x = - y
x - y = 6

x = -y
-2y = 6 / :-2

x= 3
y = -3


b.) y = x + 3
2x + y = 9

y = x+3
3x +3=9 /-3 , :3

x=2
y = 2+ 3 =5


c.) x - 4y = 15
y = 4x

y=4x
x - 16x = 15 / :-15

x = -1
y= 4 * (-1) = -4

e.) -3x = 2y
y = 1 - x

y=1-x
-3x=2 -2x/+2x

y=1-x
-x=2 /:-1

x=-2
y= 1- 2 = -1

f.) 5x + 6y = 8
x = 4y - 1

x=4y -1
20y -5 +6y =8 /+5

x=4y-1
26y = 13 /:26

y = 0,5
x= 2-1 = 1

pozdrawiam ;)
2 5 2
2010-01-16T13:12:13+01:00
A)
x= -y
x-y=6

x= -y
-y-y=6

x=-y
-2y=6 /:(-2)
y= -3

x= -(-3)
y= -3

x=3
y= -3

b)
y=x+3
2x+y=9

y=x+3
2x+x+3=9

y=x+3
3x=6 /:3

y=x+3
x=2

y=2+3
x=2

x=2
y=5

c)
x-4y=15
y=4x

x-4*4x=15
y=4x

x-16x=15
y=4x

-15x=15 /:(-15)
y=4x

x= -1
y= 4*(-1)

x= -1
y= -4

e)
-3x = 2y
y = 1 - x

-3x=2(1-x)
y=1-x

-3x=2-2x
y=1-x

-x=2 /:(-1)
y=1-x

x= -2
y=1-(-2)

x= -2
y=3

f)
5x + 6y = 8
x = 4y - 1

5(4y-1) +6y=8
x=4y-1

20y-5+6y=8
x=4y-1

26y=13 /:26
x=4y-1

y= 1/2
x= 4* 1/2 -1

x=2-1
y= 1/2

x=1
y= 1/2